Nilai-nilai Toleransi dalam Islam pada Buku Tematik Kurikulum 2013 - Evi Fatimatur Rusydiyah; Eka Wahyuni Hidayati (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2015)
This article discusses the values of tolerance found in the thematic text-book of 2013 curriculum. The thematic text-book has an important role in building students? character, especially regarding the values of tolerance. This article aims to answer questions concerning the design of tolerant attitude in the thematic text-book for class one of elementary school, the advantage and deficiency of the book, and solutions for thematic text-book regarding tolerant attitudes. As a study of documentation, this article deals with eight themes on thematic text-book for class one of elementary school. In analyzing the data, this study refers to seven indicators of tolerant attitude using content analysis method. This study concludes that the design of tolerant attitudes consists of respect, collaboration, help, friend-ship, equality, harmony, freedom of worship. The advantage of the text-book is its identification of seven indicators, while its deficiency is related to the presence of pictures contradictory to the values of tolerance. The solution for its deficiency is to revise the explanation of words in the negative pictures very to contradict the values of tolerance.